Combined effect of lasioglossin LL-III derivative with azoles against Candida albicans virulence factors: biofilm formation, phospholipases, proteases and hemolytic activity - Vaňková, Eva; Kašparová, Petra; Dulíčková, Nikola; Čeřovský, Václav (FEMS yeast research, 2020)
Candida albicans has several virulence factors at its disposal, including yeast-hyphal transition associated with biofilm formation, phospholipases, proteases and hemolytic activity, all of which contribute to its pathogenesis. We used synthetic derivative LL-III/43 of antimicrobial peptide lasioglossin LL-III to enhance effect of azoles on attenuation of C. albicans virulence factors. LL-III/43 was able to inhibit initial adhesion or biofilm formation of C. albicans strains at 50 µM. Azoles, however, were ineffective at this concentration. Using fluorescently labeled LL-III/43, we observed that peptide covered C. albicans cells, partially penetrated through their membranes and then accumulated inside cells. LL-III/43 (25 µM) in combination with clotrimazole prevented biofilm formation already at 3.1 µM clotrimazole. Neither LL-III/43 nor azoles were able to significantly inhibit phospholipases, proteases, or hemolytic activity of C. albicans. LL-III/43 (25 µM) and clotrimazole (50 µM) in combination decreased production of these virulence factors, and it completely attenuated its hemolytic activity. Scanning electron microscopy showed that LL-III/43 (50 µM) prevented C. albicans biofilm formation on Ti-6Al-4 V alloy used in orthopedic surgeries and combination of LL-III/43 (25 µM) with clotrimazole (3.1 µM) prevented biofilm formation on urinary catheters. Therefore, mixture of LL-III/43 and clotrimazole is suitable candidate for future pharmaceutical research.
Keywords: Candida albicans; Virulence Factors; Azoles; Antifungal Agents; Hydrophobic and Hydrophilic Interactions; erytrocyty; hemolýza; kationické antimikrobiální peptidy; lidé; Phospholipases; proteasy; Peptide Hydrolases; Erythrocytes; hydrofobní a hydrofilní interakce; Hemolysis; azoly; Antimicrobial Cationic Peptides; biofilmy; antifungální látky; Biofilms; faktory virulence; fosfolipasy; Humans